Quizizz Paper Mode Media Development Material Diversity Culture and Wisdom Local Class IV MIN 9 Medan - Adinda Nadda Namira; Dewi Chairunnisa Siregar; Rahma Alia; Rili Ritami Sipahutar; Eka Yusnaldi (Sean Institute, 2024)
The use of Quizizz learning media is an effort to overcome the problem of traditional learning media by adopting information and communication technology (ICT) to increase student learning competence and motivation. Quizizz is an online application-based learning media that includes quizzes, surveys, games, and discussion features. This application contains learning material presented in the form of interactive questions with various themes at various educational levels and subjects. This research aims to develop quizizz paper mode learning media for material on cultural diversity and local wisdom in science subjects for class IV MIN 9 Medan students. Apart from that, the quizizz paper mode media that was developed also aims to produce products that can measure the validity and practicality of the media in science and science learning, especially regarding material on cultural diversity and local wisdom. Thus, the effectiveness of this media is expected to be beneficial for class IV students in science and technology subjects. The research method used is Research and Development (R&D) by applying the ADDIE development model. The sample involved in this research was 30 students from class IV MIN 9 Medan. The research results show that the quizizz paper mode of learning media is said to be effective and can be used to support the science and science learning process by providing media that helps students and teachers understand the material better.